Oficina de memória: prática social de oportunidade para o envelhecimento ativo - Gonçalves, Isabel Cristina de Souza (2015)
It is not rare that elderly not diagnosed with dementia are worried about their memory loss and look for private or public services program aiming to stimulate memory. Presently, it is normal on such programs to have Memory Trainings. This tendency is bringing to light a praxis, that from my point of view deserves to be investigated, because it immediately creates an association between memory stimulation and health promotion for the elderly. After justifying such realization, I would like to clarify that the main objective of this work was to investigate, from one side, the nature of the articulation between memory and active ageing and on the other side to explore the demand behind the participation of the elderly in Memory Trainings. The investigation was oriented by facing the following specific objectives: explore deeply the responses from the institutional proposal of memory work; verify elderly profile attended on the Program of Integral Attention to Elderly (PAIE) of University of Taubaté (UNITAU), as well as professionals who are executing or who executed the activities proposed, investigate if elderly have or had memory complaints and how it is (was) received and worked on those Trainings, identify which type of memory conceptions, ageing and oldness determine or determined professional actions, discuss the results of investigation, taking in consideration how the experience accumulated on PAIE could contribute to professional training. And in the same way how my professional formation as Speech Therapist and Social Gerontology Researcher could contribute specifically to the activities performance in order to optimize memory on oldness. Referring to the Research Methodology I would like to explain that at first I made a bibliographical review which involved and articulated questions related to memory , ageing and oldness in Gerontology field and similar areas. The result of this incursion through literature on this subject can be found on Chapters 1 and 2. The thesis also counted on a field research. The methodological option of the study was a qualitative mark. It happened because, in certain way, my interest was addressed to the search of the meaning attributed to the memory by the elderly and by who was/were responsible by the proposal and accomplishment of Memory Trainings at PAIE-UNITAU. The results of this work are in the chapter 3. To this end, it was possible to conclude that maybe the originality of my work is in the exploration, in the addressed reflection and in the nature of the relation between language and memory. And from this perspective it can ratify the way already showed by Brandão (1999,2002) that, from my point of view, it has to be widely unfolded on the proposals of Memory Trainings with elderly: to be in a privileged place to hearing them, exploring widely their autobiographical narratives. Our culture, in general, and each of us, in particular, have nothing to lose if the word can be returned to these voices, which in the majority were muted (reason for its remarkable oblivion?) in a contemporary society. The accomplishment of this research was approved by Comitê de Ética e Pesquisa - PUCUSP under the number 47424415.9.0000.5482